GENOTYPIC VARIABILITY & ASSOCIATION STUDIES OF YIELD AND RELATED TRAITS OF WHEAT GROWN UNDER WATER STRESS CONDITIONS - RAUF, A; KHAN, MF; RAMZAN, A; ABIDEEN, ZU; MUNAWAR, I (Biological and Clinical Sciences Research Journal, 2023)
Climate Change is a serious risk to crops as it harnesses the survival of plants and is a major cause for drought stress in many areas of the world including Pakistan. Most of the cultivated area in Pakistan is vulnerable to drought conditions brought about by climate change, leading to fewer productive harvests. Wheat is Pakistan’s major staple food crop, but it needs to be enhanced and developed to be more tolerant to drought conditions. We all know that future water crisis would affect us in many ways, and we need plant, which can cope up with water deficiency, otherwise it will be leading grains type of country in near future. To investigate the drought tolerance in wheat, we cultivated fifteen wheat genotypes in a dry and arid region of Layyah under water stress. The plants were irrigated at the initial stages and left them to grow outdoors without irrigation for six weeks. The study’s objective was to evaluate these mutants’ performance under drought stress. Data were collected for yield and yield-related traits, including plant height, number of tillers, number of spikes, spike length, number of spikelets per spike, grains per spike (each with a part), and grain yield. Underwater, stress conditions, there were significant differences in all the parameters. In the experiment, genotypes Barani-83 and Subhani-21 were drought-tolerant and significantly increased parameters such as the number of grains per spike and grain yield. These parameters can be used as selection criteria for breeding programs of drought-tolerant varieties.